Forward Genetics Approach Reveals a Mutation in bHLH Transcription Factor-Encoding Gene as the Best Candidate for the Root Hairless Phenotype in Barley - Gajewska, Patrycja; Janiak, Agnieszka; Kwasniewski, Miroslaw; Kędziorski, Piotr; Szarejko, Iwona (Frontiers in Plant Science, 2018)
Root hairs are the part of root architecture contributing significantly to the root surface area. Their role is particularly substantial in maintaining plant growth under stress conditions, however, knowledge on mechanism of root hair differentiation is still limited for majority of crop species, including barley. Here, we report the results of a map-based identification of a candidate gene responsible for the lack of root epidermal cell differentiation, which results in the lack of root hairs in barley. The analysis was based on the root hairless barley mutant rhl1.b, obtained after chemical mutagenesis of spring cultivar ‘Karat’. The rhl1 gene was located in chromosome 7HS in our previous studies. Fine mapping allowed to narrow the interval encompassing rhl1 gene to 3.7 cM, which on physical barley map spans a region of 577 kb. Five high confidence genes are located within this region and their sequencing resulted in the identification of A>T mutation in one candidate, HORVU7Hr1G030250 (MLOC_38567), differing the mutant from its parent variety. The mutation, located in the 3′ splice-junction site, caused the retention of the last intron, 98 bp long, in mRNA of rhl1.b allele. This resulted in the frameshift, the synthesis of 71 abnormal amino acids and introduction of premature STOP codon in mRNA. The mutation was present in the recombinants from the mapping population (F2rhl1.b × ‘Morex’) that lacked root hairs. The candidate gene encodes a bHLH transcription factor with LRL domain and may be involved in early stages of root hair cell development. We discuss the possible involvement of HORVU7Hr1G030250 in this process, as the best candidate responsible for early stages of rhizodermis differentiation in barley.